Drought surveillance in Sri Lanka. - Copernicus Global Land Service (Copernicus Global Land Service, 2017)
Case study related to Sri Lanka. IWMI developed the South Asia Drought Monitoring System (SADMS) which was further improved by devising the Soil Water Anomaly Drought Index (SWADI) in order to forecast drought impacts on agriculture on a regular basis. Together with other tools, SADMS is able to support contingency planning at national and regional levels. The knowledge products are regularly shared with the Disaster Management Centre, to mitigate drought risks and addressing improved food security.